2020
DOI: 10.1021/acsanm.0c01592
|View full text |Cite
|
Sign up to set email alerts
|

Reusable Graphitic Carbon Nitride Nanosheet-Based Aerogels as Sorbents for Oils and Organic Solvents

Abstract: Increasing oily wastewater and frequent oil leakage accidents have become a serious global environmental problem. To improve the adsorption capacity and simplify the recovery process of crude oil, it is a great significance to develop various advanced oil adsorbents and oilcollecting devices. In this work, a lightweight and compressible threedimensional (3D) g-C 3 N 4 /poly(vinyl alcohol) (PVA) nanosheet-based aerogel was successfully fabricated. The resulting 3D g-C 3 N 4 /PVA nanosheet-based aerogel has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Song et al reported a compressible 3D g-C 3 N 4 /PVA nanoflake aerogel. 135 Low density and high hydrophobicity endow the aerogel the ability to float on the water surface, which was more conducive to the solution of oil spills. In addition, the high mechanical strength and compressibility enable the aerogel to complete the renewable steps such as cyclic distillation, extrusion and combustion, and the adsorption capacity decreases little after the renewable cycle.…”
Section: Adsorption and Removal Of Pollutantsmentioning
confidence: 99%
“…Song et al reported a compressible 3D g-C 3 N 4 /PVA nanoflake aerogel. 135 Low density and high hydrophobicity endow the aerogel the ability to float on the water surface, which was more conducive to the solution of oil spills. In addition, the high mechanical strength and compressibility enable the aerogel to complete the renewable steps such as cyclic distillation, extrusion and combustion, and the adsorption capacity decreases little after the renewable cycle.…”
Section: Adsorption and Removal Of Pollutantsmentioning
confidence: 99%
“…One way of overcoming these problems may be the use of CNNs as functional nanofillers in composite materials. Nonetheless, although many works have been reported on the synthesis and the applications of CN-based materials, there is still a very limited number of studies on the development of CN porous polymer-based composites for chemosensing alone or combined with the removal of water contaminants. For example, CNNs were introduced into polymer gel structures, such as polyacrylamide-based composites as well as acrylic resins for the removal of organic and inorganic pollutants. The use of CNNs for the surface functionalization of the commercial ultrafiltration membranes and their incorporation into surface coatings has also been reported in terms of the development of antifouling dye and salt filters.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm these words, we give here only one reference. [ 24 ] In this work, it was shown that a three‐dimensional aerogel based on g‐C 3 N 4 /PVA nanosheets can absorb various oils and organic solvents in an amount exceeding its weight by 228–695 times. Moreover, after 40 sorption–desorption cycles, the structure of 3D aerogels based on g‐C 3 N 4 /PVA nanosheets is preserved, and the adsorption capacity remains at the level of 93–95%.…”
Section: Introductionmentioning
confidence: 99%